Energy system diagnosis of paper-drying process, Part 2: A model-based estimation of energy-saving potentials. Issue 10 (26th July 2016) - Chen, Xiaobin; Li, Jigeng; Liu, Huanbin; Yin, Yongjun; Zhang, Yanzhong
ABSTRACT: The pulp and paper sector is the fourth largest industrial sector in terms of energy use in the world. Of the numerous processes involved in paper-making by a paper machine, the dryer section is the process that consumes the largest amount of energy. A model-based method for estimating energy-saving potentials of the dryer section was put forward in the present study. It was done by four steps: establishing a mathematical model about energy consumption, determining the model parameters, benchmarking the drying performance to obtain the corresponding energy-saving measures, and estimating the energy-saving potentials by using the mathematical model. In a case study, a multi-cylinder dryer section was selected to illustrate the method. After a fundamental field test and observation, several operating problems that restricted the energy performance of paper drying were found. And then several reasonable energy-saving measures were suggested to the operators. Finally, applying the mathematic model, it was found that 0.32 ton of steam will be saved when producing 1 ton of paper in recommended operating conditions. With the designed capacity of 200, 000 tons/year, the annual steam-savings will be 64, 000 tons. Generally, the price of steam is 130–150 Chinese Yuan (about US21–24) in China, and the annual economic benefits will be 8.32–9.60 million Chinese Yuan (about US1.344–1.536 million).